The roles of C-reactive protein-albumin ratio as a novel prognostic biomarker in heart failure patients: A systematic review - Kurniawan, Roy Bagus; Oktafia, Pratista; Saputra, Pandit Bagus Tri; Purwati, Dinda Dwi; Saputra, Mahendra Eko; Maghfirah, Irma; Faizah, Novia Nurul; Oktaviono, Yudi Her; Alkaff, Firas Farisi (Current problems in cardiology, 2024)
•CAR is significantly associated with in-hospital mortality and out-hospital mortality due to all causes in patients with acute and chronic heart failure (HF).•The diagnostic performance of CAR in predicting mortality is considered acceptable, ranging from 0.73-0.78 area under curve (AUC).•CAR is not clinically and statistically associated with lower left ventricular ejection fraction (LVEF), but it is associated with higher hospitalization rate, number of hospitalizations, severity of NYHA class, and risk of advanced HF.•High CAR is associated with higher complications, organ failures, the need for defibrillator shock, as well as invasive and non-invasive ventilations. C-Reactive Protein (CRP)-albumin ratio (CAR) is a novel prognostic biomarker that is predicted to be a more reliable indicator than CRP or albumin alone. Therefore, this systematic review aimed to evaluate the role of CAR in predicting poor outcomes of heart failure (HF) patients. We conducted a literature search across ProQuest, PubMed, ScienceDirect, Web of Science, and Scopus. All related studies assessing CAR and reporting mortality outcomes or other adverse outcomes were assessed. A total of five studies with a total of 1821 patients were included in this review. CAR is significantly associated with all-causes in-hospital mortality and out-hospital mortality in patients with acute and chronic heart failure. CAR is associated with higher hospitalization rates, the number of hospitalizations, severe New York Heart Association (NYHA) classification, and the risk of advanced HF. In conclusion, CAR is significantly associated with poor HF outcomes including all-cause mortality (cardiac and non-cardiac death).